Proceso de atención de enfermería en paciente menor de 5 años con desnutrición crónica más anemia. - Monroy Barragán, Jessica Gladys (2019)
Chronic malnutrition is one of the pathologies that presents a severe infantile caloric protein alteration that frequently occurs in children under 5 years of age, making it one of the main problems in Ecuador. The purpose of carrying out this clinical case is to establish the correct interventions of the nursing staff and to point out the problems that may occur during the evolution of this pathology, and in turn the main factors involved in its improvement. This case study was carried out in a 3-year-old female patient with a medical diagnosis of chronic malnutrition plus anemia, which was detected and treated for prompt improvement. Information was collected from the beginning of the pathology to the present, so we see the evolution of it and, in turn, a full nursing assessment is carried out through the eleven functional patterns of Marjory Gordon and with respect to this, interventions are proposed to facilitate the care and improvement and quality of life for the patient and the family. It should be noted that by collecting information we establish the descriptive methodology in contact with reality to observe, describe and control the pathology and will also be based on bibliography to give more support and veracity to scientific work.